Soybean Plant Growth and Production Response (Glycine max (L.) Merril) to the Application of Liquid Organic Fertilizer (Poc) Apu – Apu (Pistia stratiotes L.) Plant and Various Soil Reformers on Ultisol Soil Media - Ellen Lumisar Panggabean; Azwana Azwana (Biology, Medicine, & Natural Product Chemistry, 2025)
This study aimed to evaluate the growth and yield responses of soybean (Glycine max L. Merr.) to the application of liquid organic fertilizer (LOF) derived from apu-apu (Pistia stratiotes L.) and various soil conditioners on Ultisol soil. The research was carried out from September to December 2020 at the experimental garden of the Faculty of Agriculture, Universitas Medan Area, located at an altitude of 22 masl with flat topography, Ultisol soil characteristics, and a soil pH of 4.94. The experimens used a randomized block design with two factors: (1) concensrations of apu-apu LOF (0%, 25%, 50%, and 75% per liter of water) and (2) types of soil conditioners (no conditioner, rice-husk biochar, Mucuna bracteata green manure, and human-hair organic amendmens at 50 g per polybag). Observed parameters included plans height, number of branches, flowering age, number of bunches per plans and per plot, number of pods per plans and per plot, seed weight per plans and per plot, and 100-seed dry weight. The results showed that the application of LOF from apu-apu significansly increased several agronomic and yield componenss, namely number of branches at 6 WAP, number of bunches per plans and per plot, number of pods per plans and per plot, seed weight per plans and per plot, and 100-seed dry weight. Meanwhile, the application of differens soil conditioners produced highly significans effects on plans height at 4–6 WAP, number of pods per plant and per plot, seed weight per plans and per plot, and 100-seed dry weight, although it did not significansly affect the number of branches or number of bunches. Overall, the combination of LOF and soil conditioners improved soybean growth and productivity in Ultisol soil conditions.